SAT0463 Polyautoimmunity and clustering of autoimmune diseases. (23rd January 2014) - Rojas-Villarraga, A.; Amaya-Amaya, J.; Lopez-Kleine, L.; Guarin-Parra, M.R.; Rodriguez-Rodriguez, A.; Mantilla, R.D.; Anaya, J.M.
Abstract : Objectives: To identify polyautoimmunity and to search for a grouping pattern of autoimmune diseases (ADs). Methods: This was a cross-sectional analytical study in which 1083 consecutive patients with rheumatoid arthritis (n=304), systemic lupus erythematosus (SLE, n=335), systemic sclerosis (n=290), and multiple sclerosis (n=154) were assessed for the coexistence of 23 ADs. Factors associated with polyautoimmunity were evaluated by multivariate analyses. A systematic literature review was done for all multiple autoimmune syndrome (MAS) cases up to 2011, which were analyzed using a distance measure adapted from the Rogers and Tanimoto coefficient for symmetric binary data. Then, clusters were obtained by using the hclust function implemented in R software. Results: Polyautoimmunity was observed in 373 patients (34.4%). Autoimmune thyroid disease (AITD) and Sjögren's syndrome (SS) were the most frequent diseases encountered. Female gender and familial autoimmunity were associated with polyautoimmunity. A dendogram based on 226 MAS cases from 142 articles retrieved was built (figure). AITD followed by SLE and SS were the most hierarchical diseases encountered and thus the most representatives of polyautoimmunity. Conclusions: Results indicate that coexistence of ADs is not uncommon and follows a grouping pattern. Polyautoimmunity is the term proposed for this association of disorders, which encompasses the concept of a common origin for these diseases. It is our contention that the term "secondary diseases" should not longer be used because it detracts from the reality that these patients have two or more well-established ADs sharing the same etiopathogenesis. Disclosure of Interest: None Declared